The Effect of Quickness Training Using Reaction Ball Media on Improving Futsal Goalkeeper Reaction - mochamad renaldi; Mochamad Yamin Saputra; Ivan Rivan Firdaus; Mulyana (Universitas Negeri Semarang, 2024)
Futsal is played by 5 players, one of whom is a goalkeeper. Futsal goalkeepers really need reactions to anticipate the ball from entering the goal. The problem faced by goalkeepers is reaction and reflex in playing, and to improve the reaction, reaction ball media can be used as quickness training. This study aims to provide an understanding of the importance of futsal goalkeeper reactions in playing. Goalkeeper reaction training can provide significant benefits in improving physical performance. This study uses an experimental method and a quantitative approach with a one group pre-test-post-test design. The population used in this study were extracurricular goalkeepers of of junior high school 23 Bandung aged 13-15 years and male. With a total of 10 goalkeepers of of junior high school 23 Bandung, with a purposive sampling technique. The study used one test instrument, namely a test to measure the goalkeeper’s reaction speed using a whole body reaction tool. The data was processed and analyzed using SPSS version 25. The results of the study showed thatQuickness training using reaction ball media has an effect on improving futsal goalkeeper reactions. It can be concluded that to improve futsal goalkeeper reactions, one of which is using reaction ball media, of course with a structured program.